The Threats of Ai and Disinformation in Times of Global Crises - Mukhtar Imam (Bulletin of Islamic Research, 2025)
This study aims to investigate the threats posed by artificial intelligence (AI)-enabled disinformation during global crises, including pandemics, geopolitical conflicts, and climate emergencies. While prior research has examined AI’s role in enhancing information processing and communication, few studies have critically analyzed how AI tools such as deep-fakes, NLP-generated fake news, and social media bots are systematically weaponized to distort facts and manipulate public perception at scale. This research addresses that gap by offering a thematic and case-based analysis of AI-driven disinformation campaigns during crisis periods. Using a qualitative descriptive design, this study employs library research and digital observation methods to analyze a variety of sources—academic publications, digital media artifacts, and case studies—related to disinformation. Data were collected through purposive sampling of literature and observed disinformation trends on social platforms. The data were analyzed thematically to classify the types of AI-assisted disinformation and examine their social, political, and psychological impacts. The results reveal that AI technologies significantly amplify the scale, speed, and believability of disinformation. Deep-fake content was found to influence public opinion by mimicking credible figures, while NLP-generated fake news exploits confirmation bias to spread ideologically charged narratives. Meanwhile, AI bots disrupt online discourse by creating echo chambers and undermining trust in public institutions. These dynamics were particularly evident in the COVID-19 pandemic, the Russia-Ukraine conflict, and climate change denial movements. The novelty of this study lies in its integrated approach to mapping AI-powered disinformation as both a technological and socio-political phenomenon. It proposes a tripartite mitigation framework involving technological detection systems, regulatory policy interventions, and media literacy campaigns to enhance societal resilience. This research contributes to the growing discourse on information disorder by offering a critical lens on how AI can both exacerbate and help solve the global crisis of trust and truth.